Analysis Of Best-Selling Accessories In The Wiwid Collection Using The Moora Method - Susana Susana; Fauriatun Helmiah; Maulana Dwi Sena (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Medication logistics management is a critical aspect of supporting healthcare Wiwid Collection is a business selling various types of accessories located in Perk Sei Balai (Lolotan), Dusun 3 Sukajadi, Batu Bara Regency, North Sumatra. Wiwid Collection faces various challenges in determining best-selling accessories that are most in demand by consumers. Difficulties in identifying superior products persist because product selection is based on guesswork and not based on structured sales data analysis. This often leads to inaccurate decisions regarding stock management and marketing strategies. To address these issues, a Decision Support System (DSS) using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method is needed, capable of processing accessory sales data in a structured and systematic manner based on assessment criteria including stock, sales quantity, price, and purchase time. The purpose of this research is to design and build a computerized system capable of assisting decision-making in determining best-selling accessories at Wiwid Collection. The Multi-Objective Optimization by Ratio Analysis (MOORA) method is one of the methods used in Decision Support Systems (DSS). The research method used is quantitative, a research method that prioritizes the collection and analysis of quantitative data in the form of numbers, statistics, and mathematical formulas. Based on the research results, the alternative preferences for best-selling accessories are ranked 1 (Long Socks), 2 (Bead Bracelets), 3 (Chinese Rubber), 4 (Star Clips), and 5 (Rings)